Organic Mechanoluminescence with Aggregation‐Induced Emission. Issue 21 (26th September 2018) - Ubba, Eethamukkala; Tao, Yu; Yang, Zhiyong; Zhao, Juan; Wang, Leyu; Chi, Zhenguo
Abstract: Mechanoluminescence (ML) involves the emission of light from various organic and inorganic materials upon mechanical stimulus. In this review, we contemplate the advances of metal‐free, purely organic ML compounds with aggregation‐induced emission (AIE), which give strong emission upon mechanical force. We show the new ML‐AIE based materials can be used explore the basic of ML properties with structure–property relationships and molecular interactions. The flourishing idea of ML‐AIE may help to find the characteristic and elusive component of ML as it partners with AIE, which upgrades the emission property in solids or aggregates. Recent advances in ML‐AIE information could increase the wide scope of research in this expanding area, as these materials have promising applications in different optoelectronic areas. Abstract : Glowing on grinding : Mechanoluminescent (ML) materials have seen remarkable breakthroughs in recent years. It has been discovered that many ML materials also display aggregation‐induced emission (AIE) properties. In this focus review, ML materials and ML‐AIE materials are summarized to established the relationship between ML properties and molecular arrangements (molecular aggregation packing modes, strong intermolecular interactions, and symmetries).